GAYA KEPEMIMPINAN DALAM DILEMA ETIS: TINJAUAN LITERATUR GAYA KOMUNIKASI KEPEMIMPINAN - Rakhma, Meyla Tazqiya; Nur Fadhilah, Salma Nisrina; Zhillani, Fahmi Muhammad; Yulianita, Neni (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2022)
Having an important role in an organization, leadership style is one of the determining things in the success of the organization. However, being part of a country based on laws and customs makes leadership often tied to existing ethics, so the term ethical leadership emerges. The purpose of this article is to explore and examine more deeply the basic differences between ethical and unethical leadership styles in an organization. By using a literature review approach and a review of social exchange theory and social identity theory, the observations show that ethical leadership is associated with two dimensions, namely moral person and manager morale with additional characteristic components such as fairness, integrity, ethical guidance, people-orientation, power-sharing, clarification. roles, and concern for sustainability. Then the unethical leadership is shown in two leadership categories, namely the hypocritical leader characterized by hypocrisy, and the ethically neutral leader characterized by self-oriented nature.